Identification of Sperm mRNA Biomarkers Associated with Sex-Determination in Korean Native Cows - Kwan-Sik Min; Munkhzaya Byambaragchaa; Hyun Kim; Myung-Hum Park (The Korean Society of Animal Reproduction and Biotechnology, 2019)
This study was conducted to analyze the specific genes associated with sex-determination in Korean native cow. The highly organized spermatogenesis requires accurate spatial and temporal regulation of gene expression, which is governed by transcriptional, post-transcriptional, and epigenetic processes. Recently, farmers have been interested in determining the sexual identity of the calves in their farm. We analyzed the sperm of Korean native and Holstein cows, which were supplied from Hanwoo Improvement Center. We evaluated sperm motility and expression of sperm-specific genes after treating semen with both male- and female reagents. Sperm motility in Korean native cows decreased by approximately 10% in the first 30 minutes after treatment with sex-determination reagent. However, sperm motility of Holstein cows decreased to 60-70% after 15 minutes and to 20-30% after 30 minutes. We selected six specific genes expressing in the spermatozoa to analysis the gene expression level. The Real-time PCR results suggest that the selected genes (Gimap4, Tmeff1, Rac2, Abi2, Rac1, and Clu) were highly expressed in the group treated with the male reagent compared to the group treated the female reagent and to the untreated-group (control). In the present study, we suggest that the selected genes play a pivotal role in sex-determination.